Non-tuberculous Mycobacteria in South African Wildlife: Neglected Pathogens and Potential Impediments for Bovine Tuberculosis Diagnosis - Gcebe, Nomakorinte; Hlokwe, Tiny M. (Frontiers in Cellular and Infection Microbiology, 2017)
Non tuberculous mycobacteria (NTM) are not only emerging and opportunistic pathogens of both humans and animals, but from a veterinary point of view some species induce cross-reactive immune responses that hamper the diagnosis of bovine tuberculosis (bTB) in both livestock and wildlife. Little information is available about NTM species circulating in wildlife species of South Africa. In this study we determined the diversity of NTM isolated from wildlife species from South Africa as well as Botswana. Thirty known NTM species and subspecies, as well as unidentified NTM , and NTM closely related to Mycobacterium goodii/ Mycobacterium smegmatis were identified from 102 isolates cultured between the years 1998-2010, using a combination of molecular assays viz PCR and sequencing of different Mycobacterial house- keeping genes as well as single nucleotide polymorphism (SNP) analysis. The NTM identified in this study include the following species which were isolated from tissue with tuberculosis- like lesions in the absence of Mycobacterium tuberculosis complex (MTBC) implying their potential role as pathogens of animals: Mycobacterium abscessus subsp bolletii, Mycobacterium gastri, Mycobacterium species closely related to Mycobacterium goodii/ Mycobacterium smegmatis, Mycobacterium brasiliensis, Mycobacterium sinense JMD 601, Mycobacterium avium subsp avium, Mycobacterium sp GR-2007,Mycobacterium bouchedurhonense and Mycobacterium septicum/ M. peregrinum. Mycobaterium brasiliensis, Mycobacterium gastri, Mycobacterium sp GR-2007 and a potential novel Mycobacterium species closely related to Mycobacterium goodii were found for the first time in this study to be potential pathogens of animals. Mycobacterium simiae was isolated from a sample originating from a tuberculin skin test positive reactor, demonstrating its potential to elicit inappropriate immune responses in animals that may interfere with diagnosis of tuberculosis by immunology. Mycobacterium abscessus subsp bolletti was the most frequently detected NTM identified in 37 of the 102 isolates. Other NTM species were also isolated from animals not showing any pathological changes. Knowledge gained in this study contribute to the understanding of NTM species circulating in wild animals in South Africa and the pathogenic potential of certain species, whose role in disease causation need to be examined, as well as to a certain extent the potential of M. simiae to hamper the diagnosis of bTB.